2018
DOI: 10.2147/ppa.s185848
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mailed letters to improve medication adherence among Medicare Advantage Plan participants with chronic conditions

Abstract: BackgroundMedication adherence is associated with improved health outcomes in multiple chronic diseases. Information is needed on the effectiveness of specific adherence interventions. This study’s objectives were to quantify effects of a targeted mailing intervention on adherence among older adults at risk for nonadherence, and to examine associations of individual and plan characteristics with adherence.Materials and methodsAmong adults enrolled in a Medicare Advantage Plan with prescription drug coverage fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…a need to develop more practical interventions combining educational and behavioral components. 28,34,35 The European Atherosclerosis Society Consensus Panel recommends brief discontinuation and re-initiation of statin therapy in patients with statin intolerance such as statin-attributed muscle symptoms. 36 Based on the results of the present study, we found that a greater rebound effect occurs in association with withdrawal from high-intensity statins, and this is proportional to the statin intensity.…”
Section: Discussionmentioning
confidence: 99%
“…a need to develop more practical interventions combining educational and behavioral components. 28,34,35 The European Atherosclerosis Society Consensus Panel recommends brief discontinuation and re-initiation of statin therapy in patients with statin intolerance such as statin-attributed muscle symptoms. 36 Based on the results of the present study, we found that a greater rebound effect occurs in association with withdrawal from high-intensity statins, and this is proportional to the statin intensity.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study ( N = 39) showed that HE-related hospitalizations were significantly reduced in patients receiving brief (≤ 15 min), targeted outpatient education (i.e., focused on the pathophysiology of HE, maintenance of bowel movements, treatment of HE) facilitated by nurses compared with patients not receiving this intervention (HR, 0.14; 95% CI, 0.02–0.77; P = 0.02) [ 65 ]. Another study showed that almost one-quarter (24.1%) of patients ( N = 460; with chronic conditions) enrolled in a Medicare Advantage program who were identified as nonadherent to treatment and unresponsive to telephone calls became adherent following receipt of a mailed reminder to refill their maintenance prescription(s) [ 66 ].…”
Section: Reducing Risk Of He-related Hospitalizations In Patients Wit...mentioning
confidence: 99%